V ibrio aestuarianus clade A and clade B isolates are associated with Pacific oyster ( Magallana gigas ) disease outbreaks across Ireland - Coyle, Nicola; O'Toole, Ciar; Thomas, Jennifer C. L.; Ryder, David; Feil, Edward; Geary, Michelle; Joseph, Andrew Wokorac; Waine, Ava; Cheslett, Deborah; Verner-Jeffreys, David W (Microbial Genomics, 2023)
Bacteria from the family Vibrionaceae have been implicated in mass mortalities of farmed Pacific oysters (Magallana gigas) in multiple countries, leading to substantial impairment of growth in the sector. In Ireland there has been concern that Vibrio have been involved in serious summer outbreaks. There is evidence that Vibrio aestuarianus is increasingly becoming the main pathogen of concern for the Pacific oyster industry in Ireland. While bacteria belonging to the Vibrio splendidus clade are also detected frequently in mortality episodes, their role in the outbreaks of summer mortality is not well understood. To identify and characterize strains involved in these outbreaks, 43 Vibrio isolates were recovered from Pacific oyster summer mass mortality episodes in Ireland from 2008 to 2015 and these were whole-genome sequenced. Among these, 25 were found to be V. aestuarianus (implicated in disease) and 18 were members of the V. splendidus species complex (role in disease undetermined). Two distinct clades of V. aestuarianus – clade A and clade B – were found that had previously been described as circulating within French oyster culture. The high degree of similarity between the Irish and French V. aestuarianus isolates points to translocation of the pathogen between Europe’s two major oyster-producing countries, probably via trade in spat and other age classes. V. splendidus isolates were more diverse, but the data reveal a single clone of this species that has spread across oyster farms in Ireland. This underscores that Vibrio could be transmitted readily across oyster farms. The presence of V. aestuarianus clades A and B in not only France but also Ireland adds weight to growing concern that this pathogen is spreading and impacting Pacific oyster production within Europe.